Peningkatan Literasi Bahasa Inggris berbasis Pendidikan Karakter bagi Santri Rumah Tahfidz Syafa’at Qur’an - Dian Safitri; Leni Marlina; Syafitri Ramadhani; Rita Arni (Universitas Negeri Padang, 2023)
The educational scholarship offers are increasing to Al-Qur’an memorizers. It arouses their interest in learning English to have an added value in competing at national and international levels. However, the access to English learning is not widely open for the students of Rumah Tahfidz Syafa'at Qur'an since most of them are coming from low economic families. They can only rely on learning at school for a very limited time, while language exposure must be maximized from an early age for foreign language mastery. Therefore, the community service team tried to build basic English language competencies to increase their literacy through structured English learning taught through conversation and storytelling. The students were specified to those who are in 4th to 6th grade of Elementary School. Character-based learning was implemented here by integrating material with character education to build good characters in the students. It was also as a response to the issue of moral degradation which belongs to the government's focus in education. This program was carried out for 14 face-to-face meetings. The assessments included 1 Initial Knowledge Test (IKT), 2 monthly assessment, and 1 final assessment. As a result of the final assessment, they were able to introduce and describe themselves both in written and spoken form. In addition, observations were also carried out to see the achievements of the integration of character education. The results showed an increase in the 4C aspects which include communication, collaboration, critical thinking, and creativity.